2007
DOI: 10.1007/s10787-007-1595-z
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 stimulates VEGF expression in primary rat gastric fibroblasts through EP4 receptors

Abstract: Vascular endothelial growth factor (VEGF), a fundamental regulator of angiogenesis, plays an important role in gastric ulcer healing. In addition, prostaglandin E2 (PGE2), derived from cyclooxygenase-2, stimulates VEGF release in gastric fibroblasts. In the present study, we examined which EP receptor subtype is involved in the expression of VEGF in primary rat gastric fibroblasts. PGE2 stimulated VEGF protein expression in the fibroblasts in a time- and dose-dependent manner. The up-regulation by PGE2 of VEGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 14 publications
3
20
0
Order By: Relevance
“…Prostaglandin, a key molecule that stimulates the complex array of ulcer healing mechanism, gets synthesized in the mucosal cells by cyclooxygenase (COX) enzymes [33]. The increase in PGE 2 may stimulate growth factors expression in gastric mucosa and this effect may be involved in the healing promoting action of PGE 2 on gastric ulcers which is consistent with the previous findings [34].…”
Section: Discussionsupporting
confidence: 87%
“…Prostaglandin, a key molecule that stimulates the complex array of ulcer healing mechanism, gets synthesized in the mucosal cells by cyclooxygenase (COX) enzymes [33]. The increase in PGE 2 may stimulate growth factors expression in gastric mucosa and this effect may be involved in the healing promoting action of PGE 2 on gastric ulcers which is consistent with the previous findings [34].…”
Section: Discussionsupporting
confidence: 87%
“…PGE 2 was reported to stimulate the release of VEGF in rat gastric fibroblasts through the EP4 receptor (21), and in human synovial fibroblasts through the EP2 and EP4 receptors (22). The present study extends these findings in several ways.…”
Section: Discussionsupporting
confidence: 82%
“…PGE 2 exerts its actions by acting on four distinct G protein-coupled E-prostanoid (EP) receptors that produce distinctly different effects (13)(14)(15)(16). The EP1 receptor regulates Ca 21 channel gating via an unidentified G protein. The EP2 and EP4 receptors couple to G s and mediate increases in concentrations of cAMP.…”
mentioning
confidence: 99%
“…PGE 2 has been reported to induce the expression of VEGF in stromal fibroblasts, and EP2 and/or EP4 signaling is considered to be involved in the induction of VEGF (41,42). Using a gastric cancer mouse model, Guo et al (42) have reported that the PGE 2 and Wnt pathways play key roles in gastric tumorigenesis through the induction of VEGF production by stromal fibroblasts.…”
Section: Discussionmentioning
confidence: 99%